Upstream turbulence effects on the self-similarity of wakes: vortex pair dynamics - Murari, Prasanth K.; Proenca, Anderson R.; Garry, Kevin P. (American Institute of Aeronautics and Astronautics (AIAA), 2023)
A pair of counter-rotating vortices is a very common flow feature associated with aircraft and ground vehicles. This paper details the research conducted by the authors to understand the effect of upstream turbulence on a pair of counter-rotating vortices generated using a slender delta wing model with a 76° leading-edge sweep. The level of upstream turbulence is predicted to have an effect on the spatial development and decay of such vortices, which is crucial to determine safe or optimal separation distances in aerospace, automotive and motorsport applications. CFD simulations were performed for four different angles of attack (10°, 15°, 20° and 25°) by employing RANS as well as DDES turbulence modeling approaches. Wind Tunnel testing was performed by utilising passive turbulence-generating grids. Unsteady, three-dimensional velocity data is recorded for three wake locations using a 4-hole cobra probe. Self-similarity analysis of mean velocity profiles has been performed for the near-wake region to quantify the effect of turbulence on vortex characteristics. The vortices were observed to retain their functional profile even in high turbulence conditions until the three-dimensional instabilities came into play. However, increasing turbulence reduced the strength (circulation) of the vortices and amplified the three-dimensional instabilities that led to the eventual decay of the pair. The findings of this research can be further evaluated to see if a viable flow control technique can be devised to accelerate the decay of undesirable trailing vortices.